Constraining Citizenship: Presidential Threshold in Indonesia’s Judicial Framework - Akbar Sabillilah, Arfan Yanayir (UI Scholars Hub, 2026)
This research critically evaluates the constitutionality of Indonesia's Presidential Threshold as regulated by Article 222 of Law No. 7/2017, requiring political parties or coalitions to secure 20% of DPR seats or 25% of national valid votes for presidential nominations. The term “Presidential Threshold” follows Constitutional Court jurisprudence, distinguishing it from the election threshold in Article 6A(3) requiring 50%+1 votes to win the presidency and the parliamentary threshold in Article 414 requiring 4% of votes for legislative seat allocation. Through normative legal analysis of Constitutional Court decisions No. 51-52-59/PUU-VI/2008, 53/PUU-XV/2017, and 62/PUU-XXII/2024, this study examines 33 judicial reviews from 2017 to 2025. Findings reveal that the Presidential Threshold restricts political participation by marginalizing small parties and independent candidates, fostering elite-driven coalitions, and undermining electoral justice. This contravenes the 1945 Constitution's principles of people's sovereignty in Article 1(2) and equal nomination rights in Article 6A. Comparative analysis with Brazil's runoff election system, which avoids nomination thresholds, highlights Indonesia's exclusionary framework that exacerbates polarization and weakens democratic legitimacy. The study concludes the Presidential Threshold perpetuates oligarchic dominance and recommends its abolition alongside reforming Constitutional Court standing rules to enhance inclusivity, strengthen judicial accountability, and align Indonesia's electoral system with substantive democratic principles.